Strengthening Strategies for Institutional Readiness of Public Universities in the Transformation toward Public Service Agency Status: A Case Study of PTN X - Andriani, Wiwik; Zahara, Zahara; Yentifa, Armel; Herman, Lisa Amelia; Septriani, Yossi; Angriani, Ria (Universitas Negeri Padang, 2025)
This study was carried out to understand how PTN X prepares itself to become a Public Service Agency (Badan Layanan Umum or BLU). Research on this topic is still limited, especially in the context of vocational higher education, even though the transformation toward BLU has a big impact on how institutions manage their finances, governance, and human resources. The purpose of this study is to describe PTN X current level of readiness and to identify strategies that can strengthen its institutional capacity in facing the BLU transition. The study used a qualitative descriptive approach involving 15 key informants selected through purposive sampling. Data were collected through interviews, focus group discussions, and document review, and analyzed thematically to capture the main issues and strategies emerging from the transformation process. The results show that PTN X is partly ready for BLU implementation. Progress has been made in governance and planning systems, but some weaknesses remain, such as limited coordination between units, dependence on government funding, and incomplete digital integration. Leadership commitment and clear policies play a key role in maintaining progress, although bureaucratic procedures still slow down flexibility and innovation. In general, this study concludes that PTN X readiness can be strengthened through better coordination, improved financial independence, digital integration, and continuous staff development. The findings also highlight that BLU transformation is not just about meeting regulations but about changing the institutional mindset to be more adaptive and accountable. The results are expected to give insight to policymakers and other vocational institutions that are preparing for the same transition.